Burns : treatment and research - Leung, Ping-Chung; Li, Nan; Li, T. Z; Li, K. J; Yu, K. J; Zi, J. X; Tso, C. K (World Scientific, 1991)
The publication contains papers and articles that focus on the treatment of burns, including current research. Intended for professional public.
Keywords: komorbidita; Comorbidity; popáleninová medicína; popálení; Burns